Collective action against corruption in Western and non-Western countries: cross-cultural implications of the Axiological-Identitary Collective Action Model - Grigoryev, Dmitry; Gallyamova, Albina; Conway, Lucian Gideon; Zubrod, Alivia; Sabucedo, José Manuel; Dono, Marcos; Batkhina, Anastasia; Boehnke, Klaus (Frontiers in Psychology, 2024)
People sometimes protest government corruption, yet our current understanding of why they do so is culturally constrained. Can we separate pancultural factors influencing people’s willingness to protest government corruption from factors culturally specific to each socioecological context? Surprisingly little cross-cultural data exist on this important question. To fill this gap, we performed a cross-cultural test of the Axiological-Identitary Collective Action Model (AICAM) regarding the intention to protest against corruption. As a collective action framework, AICAM integrates three classical antecedents of collective action (injustice, efficacy, identity) with axiological variables (ideology and morality). A total sample of 2316 participants from six countries (Nigeria, Russia, India, Spain, USA, Germany) in a multilevel analysis of AICAM predictions showed that the positive relationship of the intention to protest corruption with moral obligation, system-based anger, and national identification can be considered pancultural. In contrast, the relationships between system justification and perceived efficacy are culturally specific. System justification negatively predicted the intention to participate only in countries with high levels of wealth, while perceived efficacy positively predicted it only in countries perceived as less corrupt. These findings highlight the importance of accounting features of socioecology and separating pancultural from culture-specific effects in understanding collective action.